Immunoglobulins in children with epilepsy: the Dutch Study of Epilepsy in Childhood - CALLENBACH, P M C (Blackwell Science Inc, 2003)
In an unselected cohort of 282 children, serum immunoglobulin (Ig) concentrations were determined shortly after the first presentation with one or more unprovoked epileptic seizures and before the start of treatment with anti-epileptic drugs (AEDs), and after 9–18 months of AEDs use. At intake, IgA, IgG1, IgG2 and IgG4 concentrations were significantly higher than published reference values in healthy age-matched controls. In a subset of 127 children, Ig levels at intake were compared with those after AEDs use for 9–18 months. IgA and IgG4 levels had decreased significantly to normal concentrations, but IgG1 and IgG3 levels increased significantly. To determine the influence of AEDs, Ig levels in children who used carbamazepine or valproic acid monotherapy were analysed separately. The use of carbamazepine was associated with a significant decrease of IgA and IgG4 levels, and the use of valproic acid with a significant decrease of IgA and increase of IgG1 levels. In conclusion, humoral immunity is already altered in children shortly after the first presentation with epileptic seizures. Whether this is the consequence of an exogenous event, and to what extent this is related to an interaction of the central nervous system and the immune system, remains to be evaluated. Treatment with AEDs, such as carbamazepine and valproic acid, is associated with significant changes of Ig (sub)class concentrations.